Mechanisms of hexameric helicases. (2nd November 2021) - Fernandez, Amy J.; Berger, James M.
Abstract: Ring-shaped hexameric helicases are essential motor proteins that separate duplex nucleic acid strands for DNA replication, recombination, and transcriptional regulation. Two evolutionarily distinct lineages of these enzymes, predicated on RecA and AAA+ ATPase folds, have been identified and characterized to date. Hexameric helicases couple NTP hydrolysis with conformational changes that move nucleic acid substrates through a central pore in the enzyme. How hexameric helicases productively engage client DNA or RNA segments and use successive rounds of NTPase activity to power translocation and unwinding have been longstanding questions in the field. Recent structural and biophysical findings are beginning to reveal commonalities in NTP hydrolysis and substrate translocation by diverse hexameric helicase families. Here, we review these molecular mechanisms and highlight aspects of their function that are yet to be understood.